1339. Results for the Supplemental Microbiological Modified Intent-to-Treat (SmMITT) Population of the RESTORE-IMI 1 Trial of Imipenem/Cilastatin/Relebactam (IMI/REL) vs. Imipenem/Cilastatin Plus Colistin (IMI+CST) in Patients with Imipenem-Nonsusceptible (NS) Bacterial Infections. (26th November 2018) - Kaye, Keith; File, Thomas; Boucher, Helen W; Brown, Michelle; Aggrey, Angela; Khan, Ireen; Joeng, Hee-Koung; Tipping, Robert; Du, Jiejun; Young, Katherine; Butterton, Joan; Kartsonis, Nicholas A; et al.
Abstract: Background: Clinical trials of new antibacterial agents in patients with carbapenem-resistant infections are critical but challenging to conduct. One challenge is identifying the study population by microbiological (micro) criteria; patients need to be identified locally to initiate effective treatment rapidly, but data standardization requires central laboratory confirmation. REL is a novel β-lactamase inhibitor that can restore imipenem activity against many imipenem-NS Gram-negative pathogens. Here we compare a supplemental analysis population based on local microbiology data (SmMITT eligibility) with the primary analysis population (mMITT) from the RESTORE-IMI 1 trial (NCT02452047) of IMI/REL vs. IMI+CST. Methods: Randomized, active-controlled, double-blind, phase 3 trial enrolled adults with hospital-acquired/ventilator-associated bacterial pneumonia (HABP/VABP), complicated intra-abdominal infection (cIAI), or complicated urinary tract infection (cUTI). Patients were mMITT-eligible if pathogens were imipenem-NS (but CST- and IMI/REL-susceptible) based on central laboratory minimum inhibitory concentration (MIC). SmMITT comprised mMITT plus all patients who met inclusion criteria only based on local laboratory MIC. Results: The SmMITT population ( n = 41 [28 IMI/REL; 13 IMI+CST]) comprised 31 from mMITT plus 10 based on local MIC; 12/41 (29%) had HABP/VABP, 8/41 (20%) cIAI, and 21/41 (51%) cUTI. The majority of differences in central vs. local MIC were 1–2 dilutions; similar numbers of patients were excluded from mMITT due to imipenem susceptibility ( n = 5) or IMI/REL-NS ( n = 4); 1 patient was CST-NS. Baseline characteristics, including infecting pathogens, were comparable in SmMITT and mMITT (SmMITT: 68% male; 46% ≥65 y; 24% APACHE II score >15; 22% creatinine clearance <60 mL/minute). Rates of efficacy outcomes (overall response, day 28 clinical response, day 28 mortality) were comparable between populations, except that response rates in patients with cIAI were higher in SmMITT (table). Conclusion: Consistency of results was demonstrated across two analysis populations in a trial of resistant pathogens. This analysis provides results supportive of expected future clinical use of IMI/REL when treatment decisions will be made based on local laboratory results. Disclosures: K. Kaye, Merck & Co., Inc.: Consultant and Research Contractor, Research grant. Melinta, Achaogen, Allergan: Consultant, Consulting fee. T. File, Bio Merieux, Curetis, Melinta, Merck, MotifBio, Nabriva, Paratek, Pfizer: Consultant, Consulting fee. H. W. Boucher, Merck & Co., Inc.: Scientific Advisor, Consulting fee. M. Brown, Merck & Co., Inc.: Employee, Salary. A. Aggrey, Merck & Co., Inc.: Employee, Salary. I. Khan, Merck & Co., Inc.: Employee, Salary. H. K. Joeng, Merck & Co., Inc.: Employee, Salary. R. Tipping, Merck & Co., Inc.: Employee, Salary. J. Du, Merck & Co., Inc.: Employee, Salary. K. Young, Merck & Co., Inc.: Employee, Salary and Stock options. J. Butterton, Merck & Co., Inc.: Employee, Salary and Stock. N. A. Kartsonis, Merck & Co., Inc.: Employee, Salary and Stocks. A. Paschke, Merck & Co., Inc.: Employee and Shareholder, Salary.